IICA action strategy at country level. Suriname 1992-1993 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
This country strategy for 1992-1993 was prepared based on instructions from IICA headquarters, and shows in general and specific terms the interest from the government, non-goverment organizations, private sector and farmers in Suriname. It also shows the areas in which IICA technical cooperation is needed to ameliorate and solve partially, some of the many problems of the agricultural sector. The table of contents includes: 1) overall economic situation of the country, employment, generation of foreign income, per capita income, problems that limit agricultural and rural development, among others; 2) an introduction with three interviews: international organizations, government level and private sector; 3) summary of the sectoral assessment: development strategy of the country, main characteristics and performance of the economy, performance of the principal economic indicators and agricultural sector; 4) components of the strategy: definition of priority areas for IICA cooperation, identification of cooperation instruments to be used, mechanisms for reaching agreement and for consultation, and resource needs. Appendicies.